The Combination of Intracranial Hemorrhage, Mesenteric Artery Thrombosis and Mesenteric Artery Dissection - Yilmaz, Mustafa; Yaman, Fatih Nazmi; Tannverdi, Alper (Derman Medical Publ, 2015)
[Abstract Not Available]